Baicalin inhibits APEC-induced lung injury by regulating gut microbiota and SCFA production. Issue 24 (25th November 2021) - Peng, Lu-Yuan; Shi, Hai-Tao; Tan, Yue-Rong; Shen, Si-Yang; Yi, Peng-Fei; Shen, Hai-Qing; Fu, Ben-Dong
Abstract : Baicalin remodeled the dysbiosis of gut microbiota and increased the production of SCFAs especially acetic acid to defend APEC infection. Abstract : Baicalin is a plant-derived flavonoid from Scutellaria baicalensis Georgi with multiple bioactivities and has a protective effect against avian pathogenic Escherichia coli (APEC) infection. However, the underlying mechanism of baicalin against APEC infection is still unknown. Therefore, we aimed to explore whether the protective effects and mechanisms of baicalin on APEC-induced lung inflammation were related to the regulation of gut microbiota. The results showed that baicalin significantly reduced APEC colonization and pro-inflammatory cytokines production, and additionally recovered air–blood barrier integrity in the lungs after APEC challenge. However, depletion of gut microbiota significantly weakened the protective effects of baicalin against APEC infection as mentioned above. Furthermore, baicalin markedly restored the dysbiosis of gut microbiota induced by APEC as well as increased the abundance of short chain fatty acid (SCFA)-producing bacteria and the production of SCFAs including acetic acid, propionic acid and butyric acid, especially acetic acid. In addition, the concentrations of acetic acid and its receptor free fatty acid receptor 2 (FFAR2) were significantly upregulated in the lung tissues after baicalin treatment. In conclusion, gut microbiota played a key role in the pharmacological action of baicalin against APEC-induced lung inflammation. Baicalin remodeled the dysbiosis of gut microbiota caused by APEC and increased the production of SCFAs, especially acetic acid in the gut, and then the increased acetate may circulate to the lungs to activate FFAR2 to defend APEC infection. Together, our study suggested that baicalin inhibited APEC infection through remodeling the gut microbiota dysbiosis and increasing the SCFA production. Furthermore, baicalin may serve as an alternative antibiotic and a novel therapeutic drug to prevent or treat APEC infection.